2016
DOI: 10.1248/bpb.b15-00642
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Manassantin A against Ethanol-Induced Gastric Injury in Rats

Abstract: Manassantin A, a neolignan isolated from Saururus chinensis, is a major phytochemical compound that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACAT) inhibitory activities. In this study, we investigated the protective effects of manassantin A against ethanol-induced acute gastric injury in rats. Gastric injury was induced by intragastric administration of 5 mL/kg body weight of absolute ethanol to each rat. The positive control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…This OME mechanism was reported for rats at doses that varied between 10 μM and 400 mg/kg, as well as 200 μM/ml in regular epithelial cell lines (MDCK) and mouse macrophage (RAW264.7) [55,56]. Reduction of lipid peroxidation (Biswas et al, 2003) Expression of superoxide dismutase (Song et al, 2016) Proton pump inhibitor Activation of the HSP70 and TGF-…”
Section: Therapeutic Effects Of Omeprazole and Suggestedmentioning
confidence: 85%
See 2 more Smart Citations
“…This OME mechanism was reported for rats at doses that varied between 10 μM and 400 mg/kg, as well as 200 μM/ml in regular epithelial cell lines (MDCK) and mouse macrophage (RAW264.7) [55,56]. Reduction of lipid peroxidation (Biswas et al, 2003) Expression of superoxide dismutase (Song et al, 2016) Proton pump inhibitor Activation of the HSP70 and TGF-…”
Section: Therapeutic Effects Of Omeprazole and Suggestedmentioning
confidence: 85%
“…In vivo and in vitro studies report inhibition of necrosis by activation of TNF-α, interleukin B [75], and proinflammatory cytokines [76]. OME at 20 mg/kg presented antioxidant activity through mechanisms associated with increased superoxide dismutase (SOD) enzyme production [77,78], as well as glutathione peroxidase (GPx) and reduced glutathione (GSH) at 30 and 40 mg/kg [51,79]. In ethanol-induced gastritis rats, OME modulated mucosal lesions through its antioxidant and anti-inflammatory activity [80].…”
Section: Antioxidant and Anti-inflammatory Effects Several In Vivo Smentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been shown in many studies, our results also indicated that ethanol consumption led to PGE2 decrease, and allantoin administration in gastritis groups was observed to increase PGE2 levels in the gastric tissue. Previously, it has been documented that allantoin increased the activity of COXs production pathways (21,23). Therefore, it is probable that increased COX1 and COX2 synthesis will cause increased PGE2 secretion in the stomach tissue.…”
Section: Discussionmentioning
confidence: 99%
“…e increase in MDA content is associated with the necrosis and apoptosis of cells [24]. SOD can exert its effects by removing oxygen free radicals from the body [25]. erefore, GSH, MDA, and SOD were measured in this study to evaluate oxidative stress levels.…”
Section: Discussionmentioning
confidence: 99%